2016
DOI: 10.1037/apl0000047
|View full text |Cite
|
Sign up to set email alerts
|

Intervention effects on safety compliance and citizenship behaviors: Evidence from the work, family, and health study.

Abstract: We tested the effects of a work-family intervention on employee reports of safety compliance and organizational citizenship behaviors in 30 healthcare facilities using a group-randomized trial. Based on Conservation of Resources theory and the Work-Home Resources Model, we hypothesized that implementing a work-family intervention aimed at increasing contextual resources via supervisor support for work and family and employee control over work time would lead to improved personal resources and increased employe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
78
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 94 publications
(86 citation statements)
references
References 85 publications
(171 reference statements)
4
78
0
4
Order By: Relevance
“…Thus, FSSB provides employees a means to better manage competing work and family demands and is especially relevant in the context of the demands of workplace aggression. Supervisors that proactively provide work–nonwork-specific support meet their employees’ need to replenish resources within and outside the work domain (Hammer et al 2015). …”
mentioning
confidence: 99%
“…Thus, FSSB provides employees a means to better manage competing work and family demands and is especially relevant in the context of the demands of workplace aggression. Supervisors that proactively provide work–nonwork-specific support meet their employees’ need to replenish resources within and outside the work domain (Hammer et al 2015). …”
mentioning
confidence: 99%
“…However, few theoretical or empirical observations exist regarding the perception of organisational justice and counterproductive work behaviours with OCB (Hammer et al, 2016). Our study expanded research in this area in several ways.…”
Section: Introductionmentioning
confidence: 74%
“…Researchers found that providing flexible work arrangements benefits group processes (Chiu and Ng, 2001;Van Dyne et al, 2007), promotes work satisfaction (Clark, 2001), and results in better employer-employee relationship (Anand et al, 2010). Additionally, it also benefits the organisation in terms of safety compliance (Hammer et al, 2016), organisational performance, and organisational citizenship behaviour (OCB) (Lambert, 2000;Sun et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Results), was designed to increase employees’ control over their work and work time and increase family supportive supervisor behavior within a 4-month organizational change process. The intervention was previously evaluated in an information technology firm for safety and performance outcomes 31 , employee well-being 32 and sleep outcomes 18 and employees’ child sleep outcomes 33 . This workplace intervention was customized and implemented in the extended care industry 34 to consist of facilitator-led sessions and activities for both employees and managers to help transition them from a time-base to a result-based work culture.…”
Section: Participant and Methodsmentioning
confidence: 99%